Asymmetric Construction of α, α‐Disubstituted Piperazinones Enabled by Benzilic Amide Rearrangement. (24th March 2023) - He, Yu‐Ping; Quan, Rui; Li, Xing‐Zi; Zhu, Jieping; Wu, Hua
Abstract: An unprecedent asymmetric catalytic benzilic amide rearrangement for the synthesis of α, α‐disubstituted piperazinones is reported. The reaction proceeds via a domino [4+1] imidazolidination/formal 1, 2‐nitrogen shift/1, 2‐aryl or alkyl migration sequence, employing readily available vicinal tricarbonyl compounds and 1, 2‐diamines as starting materials. This approach provides an efficient access to chiral C3‐disubsituted piperazin‐2‐ones with high enantiocontrol, which are exceedingly difficult to access from the existing synthetic methodologies. The observed enantioselectivity was proposed to be controlled by dynamic kinetic resolution in the 1, 2‐aryl/alkyl migration step. The resulting densely functionalized products are versatile building blocks to bioactive natural products, drug molecules and their analogues. Abstract : The first examples of enantioselective benzilic amide rearrangement for the synthesis of chiral α, α‐disubstituted piperazinones have been developed. The reaction proceeds via a high ordered sequence of imidazolidination/formal 1, 2‐aza shift/1, 2‐aryl or alkyl migration. The observed enantioselectivity was proposed to be controlled by dynamic kinetic resolution in the 1, 2‐aryl/alkyl migration step.